Understanding Sericulture through a Socio-economic Lens: Evidence from Northern Karnataka, India - MANOHAR, K. N; BELLI, R. B; BINDU, S; POOJA, V. S; BHOOMIKA RAJ, G. S (Archives of Current Research International, 2025)
The present study was undertaken to analyze the socio-economic profile of sericulture farmers in Northern Karnataka, India. Sericulture is a vital agro-based, labor-intensive enterprise that supports the livelihoods of rural populations, particularly small and marginal farmers, by offering sustainable and regular income throughout the year. It integrates various stages from mulberry cultivation to silk fabric production, thereby generating employment across a wide value chain. Karnataka stands as India’s leading silk-producing state, with Southern Karnataka historically dominating the sector due to better access to technology and support services. However, Northern Karnataka, despite having favorable conditions, lags behind in terms of awareness, adoption of scientific practices, and institutional support. This study was undertaken to analyze the socio-economic profile of sericulture farmers in Northern Karnataka to identify gaps and potential areas of intervention. Data were collected from 120 randomly selected sericulture farmers using a structured interview schedule and analyzed using descriptive statistics and inferential tests. The findings revealed that most farmers were middle-aged, had medium-sized families, and cultivated between 5 to 25 acres of land. While economic motivation among them was fairly high, their participation in training, extension contact, and use of modern sericulture technologies remained low. A significant proportion fell under the medium category in terms of experience and mass media utilization. These gaps point to the urgent need for targeted policies focusing on farmer training, extension services, credit access, market linkage, and gender-inclusive approaches. Strengthening institutional support and promoting the dissemination of innovations from research institutes can bridge the knowledge gap and enhance productivity. Therefore, with appropriate policy and capacity-building interventions, sericulture holds significant promise as a driver of rural development and socio-economic upliftment in Northern Karnataka.